JEJARING KEBIJAKAN DALAM PEMBENTUKAN PERATURAN DAERAH KOTA SEMARANG NOMOR 6 TAHUN 2012 TENTANG PENGELOLAAN SAMPAH - Muhammad Arief Permana; Sri Suwitri; Dyah Lituhayu (Journal of Public Policy and Management Review, 2013)
Issues regarding Trash is one of the main problems faced in every big city, including the city of Semarang. Formulation of Semarang Local Regulation Number 6 of 2012 on Trash Management aims to address the problem of waste from upstream to downstream. Policy formulation phase is the most crucial stage for the formulation of good policies that will creat a good implementation as well. Good Governance explicitly wants the need for an active role of the public and private sectors in the implementation and formulation so that it supports the establishment of policy networks. This research aims to explain the formulation of policy networks. This research used a qualitative descriptive method to analyze the process of formulation of policy networks. To answer the problem and purpose of this research, the authors used the theory R.A.W. Rhodes in analyzing the formulation of policy networks. The results of this research indicate that the formulation of policy networks and the only normative integration and relationship with the public has not been properly created eventhough no political interest in it. This is due to the unavailabity of larger space for the public and private sectors in the process formulation local regulation on trash management. The suggestion might be to increase public participation and private sector in the process of formulation local regulations, both the process of making an academic paper and draft regulations.